Integração de UEPS e projetos experimentais de aprendizagem no ensino de física no contexto do ensino médio integrado - Sestari, Fabiane Beatriz (2021)
High School Integrated to Professional Education aims to bring scientific knowledge closer to cultural and social knowledge, and from the working world, allowing the student not only to study basic and professional education at the same time, but also to have a defragmented education. In this context, the teaching of Physics integrated to the technical training area stands out. Based on the delimited theme, we present the research problem: What are the implications of the pedagogical intervention process from the implementation of Potentially Meaningful Teaching Units (PMTU) articulated with a methodology of Experiential Learning Projects (ELP), for the progressive mastery of the conceptual fields of Hydrostatics and Hydrodynamics, in a perspective contextualized to the technical course in Agricultural Science integrated to high school? What are the potentials and limitatios of this methodological proposal to promote curriculum integration, linking the knowledge of Physics with the technical area of Agriculture? In the search for answers to the questions, through a descriptive exploratory research, characterized as a case study, our goal was to investigate, in the process of implementing the instructional material, evidences of significant learning and the operative invariants explicitly mobilized by students in action-situations in the context of the technical Agriculture field, for the progressive mastery of the conceptual fields of Hydrostatics and Hydrodynamics, and the potentialities of this process to foster integration in the context of integrated high school education. We investigated 2nd year students of the technical course in Agriculture integrated to high school, of the IFRS Ibirubá campus. The research is based on the conceptions of integrated high school and on the cognitivist of teaching and learning theories, from Vergnaud's Theory of Conceptual Fields (TCF) and Ausubel's Meaningful Learning (TML). The results analyzed qualitatively, according to the steps of an ausubelian approach, showed that the stages of teaching organized according to the PMTU articulated with the ELP, promoted a gradual understanding of the new concepts from the identified prior conceptions. In the light of TCF we identified, from the ELP, the operative invariants mobilized and explained by the students in action-situations applied to the context of the technical area. Overall, there was evidence of significant learning in relation to the concepts and theorems developed. As a value assertion of this research, we list the possibility of dissemination and adaptation of the produced material for teaching Physics; the discussions and reflections on the teaching-learning processes and; in the perspective of integrated high school, we highlight the potential of the proposal, to promote the integration of physical concepts contextualized with the Agriculture field.